Retorika Soekarno Dalam Komunikasi Internasional AntiI Imperialisme Dan Kapitalisme - Franky Paulus Roring (FISIP Universitas Bung Karno, 2018)
AbstractThe rhetoric of calling for an assumption when we open ourselves to ideas freely different from ourselves, we have many opportunities to understand. This theory is used to explain about how Soekarno created his rhetoric in International communication with the theme of Anti Imprealism and Capitalism. He not only conveyed a message to the international world, about the consistency of thought and action against Imprealism and capitalism, which can be traced in the footsteps of his thinking, but his action was on the international stage capable of building awareness, solidarity and strength of colonized countries to rise up against, even he was able to unite solidarity of two continents of Asia and Africa. Persuasion can technically succeed by engineering three things: (1) the speaker's character, (2) the emotion of the listener, (3) the spoken word. Each of these three things is known as ethos, pathos, and logos. This is what Sukarno possesses in the inspiring rhetoric of the international world. Key Word: International Communication, Rhetoric, and Diplomacy.AbstrakRetorika ajakan menjalankan asumsi ketika kita membuka diri kita sendiri terhadap ide-ide dengan bebas yang berbeda dari diri kita, kita memiliki banyak kesempatan untuk memahami. Teori ini dipakai untuk menjelaskan bagaimana Soekarno membangun retoriknya dalam komunikasi Internasional dengan tema Anti Imprealisme dan Kapitalisme. Ia tidak hanya menyampaikan pesan kepada dunia internasional, tentang konsistensinya pemikiran dan tindakan melawan Imprealisme dan kapitalisme, yang dapat ditelusur dalam jejak pemikirannya, namun aksinya dipanggung Internasional yang mampu membangun kesadaran, solidaritas dan kekuatan Negara-negara terjajah untuk bangkit melawan, bahkan dia mampu menyatukan solidaritas dua benua Asia dan Afrika. Bujukan secara teknis dapat berhasil dengan merekayasa tiga hal : (1) karakter pembicara, (2) emosi pendengar, (3) perkataan yang disampaikan. Masing-masing dari ketiga hal tersebut dikenal dengan istilah ethos, pathos, dan logos. Inilah yang dimiliki Soekarno dalam Retorika yang menggugah dunia Internasional.Kata Kunci: Komunikasi nternasional,. Retorika, Diplomasi